2021
DOI: 10.1002/tox.23149
|View full text |Cite
|
Sign up to set email alerts
|

Nigella sativa oil protects against emamectin benzoate‐Induced neurotoxicity in rats

Abstract: This study evaluated the ameliorative impact of Nigella sativa oil (NSO) on emamectin benzoate (EMB) neurotoxicity. Thirty-five male rats were randomly allocated into 5 groups (n = 7). G1 (control): received distilled water; G2: received NSO (3 ml. Kg À1 B.W.) for 6 weeks; G3: received EMB (9 mg kg À1 B.W.) for 6 weeks; G4: was cotreated with NSO and EMB for 6 weeks; G5: was treated with EMB for 4 weeks then, received NSO for 2 weeks. All treatments were given orally every other day.EMB increased serum urea, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…In a study evaluating the curative effect of black seed oil on the neurotoxicity of emamectinbenzoate (EMB) in rat brain tissue; it is stated that EMB reduces the serum GSH-Px level, black seed oil reverses the biochemical changes caused by EMB, and increases the low GSH-Px level [22]. In a study conducted to determine the possible protective effects of black cumin oil against Propoxur-induced toxicity and oxidative stress, a broad-spectrum carbamatine insecticide in rats; it is emphasized that propoxur significantly reduces GSH-Px levels in rat brain tissue, while black cumin oil increases GSH-Px levels to the same level as the control group [23]. Alam et al [26] in their study in which the effects of thymoquinone on cardiotoxicity in rats were analyzed; while it was determined that the GSH-Px level decreased in the disease model groups, it was determined that both doses of thymoquinone suppressed this change (Alam et al [26]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study evaluating the curative effect of black seed oil on the neurotoxicity of emamectinbenzoate (EMB) in rat brain tissue; it is stated that EMB reduces the serum GSH-Px level, black seed oil reverses the biochemical changes caused by EMB, and increases the low GSH-Px level [22]. In a study conducted to determine the possible protective effects of black cumin oil against Propoxur-induced toxicity and oxidative stress, a broad-spectrum carbamatine insecticide in rats; it is emphasized that propoxur significantly reduces GSH-Px levels in rat brain tissue, while black cumin oil increases GSH-Px levels to the same level as the control group [23]. Alam et al [26] in their study in which the effects of thymoquinone on cardiotoxicity in rats were analyzed; while it was determined that the GSH-Px level decreased in the disease model groups, it was determined that both doses of thymoquinone suppressed this change (Alam et al [26]).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that post-treatment SOD levels approached the control group in groups treated with TQ, which has an antioxidant effect [22]. In a study evaluating the curative effect of Nigella sativa oil on the neurotoxicity of emamectinbenzoate (EMB) in rat brain tissue; It is stated that EMB reduces serum SOD level, black seed oil reverses biochemical changes caused by EMB and increases low SOD level [23]. In another study that analyzed the effects of thymoquinone on doxorubicin (DOX)-induced cardiotoxicity in rats; thymoquinone treatment groups were administered orally at 10 and 20 mg/kg/day.…”
Section: Table 3 Distribution Of Body and Brain Weights Of Rats Accor...mentioning
confidence: 99%
“…The formalin-fixed kidney tissue specimens were trimmed, processed for paraffin sections (5 µm thicknesses), stained with hematoxylin and eosin for histopathological examination according to Bancroft and Gamble [ 72 ]. Semiquantitation for renal lesions, including vascular, inflammatory, degenerative, and neoplastic changes, were scored according to the degree of severity as no changes (0), mild (1), moderate (2), and severe (3) changes, and the grading was determined by percentage as follows: <30% changes (mild change), 30–50% (moderate change), and >50% (severe change) [ 73 ].…”
Section: Methodsmentioning
confidence: 99%
“…The quantitative immunoreactivity of TNF-α and Bax was evaluated in the liver sections in each group as described by [ 27 ], five liver sections were examined. Immuno-reactivity was analyzed in 10 microscopical fields per each section under high-power microscopic field (×400).…”
Section: Methodsmentioning
confidence: 99%